Neuron-Specific Mitochondrial DNA Deletion Levels in Sporadic Alzheimer´s Disease - Gerschütz, Anne; Heinsen, Helmut; Grünblatt, Edna; K. Wagner, Anne; Bartl, Jasmin; Meissner, Christoph; J. Fallgatter, Andreas; Al-Sarraj, Safa; Troakes, Claire; Ferrer, Isidro; Arzberger, Thomas; Deckert, Jürgen.; et al. (Current Alzheimer Research, 2013)
Oxidative stress is implicated in the pathogenesis of neurodegenerative diseases, including sporadic Alzheimer´s disease (AD). Mitochondrial DNA (mtDNA) deletions are markers of oxidative damage and increase with age. To unravel the impact of mtDNA damage on AD development, we analyzed mtDNA deletion levels in diverse neuronal cell types of four brain regions (hippocampal CA1 and CA2 regions, nucleus tractus spinalis nervi trigemini, and the cerebellum) that exhibit differing levels of vulnerability to AD related changes at progressive Braak stages compared with age-matched controls. Neurons from these four brain regions were collected using laser microdissection, and analyzed using quantitative polymerase chain reaction (qPCR). Although, no correlation between mtDNA deletion levels and AD progression were found, the data revealed regional and cell type specific selective vulnerability towards mtDNA deletion levels. In conclusion, unexpected results were obtained as granule cells from the cerebellum and neurons from the nucleus tractus spinalis nervi trigemini of the brain stem displayed significant higher mtDNA deletion levels than pyramidal cells from hippocampal CA1 and CA2 region in age and AD.
Keywords: neuronal mitochondrial DNA